Optimized single-number quantity for rating the airborne sound insulation of constructions: Living sounds - Virjonen, Petra; Hongisto, Valtteri; Oliva, David (The Journal of the Acoustical Society of America, 2016)
ISO 717-1 [(1996). International Organization for Standardization, Geneva, Switzerland] and ASTM 413 [(2010). American Society for Testing and Materials International] define various single-number quantities (SNQs) that are commonly used to rate objectively airborne sound insulation of constructions. Recent psychoacoustic evidence suggests that none of them is appropriate for a wide range of living sound stimuli. The purpose of the study was to develop an alternative compromising SNQ for the frequency range 50–5000 Hz that explains well the annoyance caused by various airborne living sounds transmitted from the neighboring dwelling. Optimal reference spectra for different living sounds were found by mathematical optimization. Experimental data from a psychoacoustic laboratory study [Hongisto, Oliva, and Keränen (2014). Acta Acust. Acust. 100, 848–863] were utilized. The subjects (n = 59) had evaluated the disturbance of living sounds that were electrically filtered to mimic transmission through commonly used wall structures. To find a high-performing reference spectrum for living sounds in general, the optimized reference spectra were averaged over all sound types. The resulting SNQ was called Rw + C opt. The related reference spectrum deviates significantly from the reference spectrum for living activities, C 50–5000, below 315 Hz. The suggested SNQ correlates better with the subjective disturbance caused by living sounds than any of the present standardized SNQs of ISO 717-1 or ASTM 413.